S82 Multi-centre prospective comparison of the BTS and ACCP guidelines to determine size in primary spontaneous pneumothorax. (14th November 2013) - Nikolic, M; Lok, L; Mattishent, K; Barth, S; Yung, B; Cummings, N; Shulgina, L; Wade, D; Shittu, M; Vali, Y; Chong, K; Wilkinson, A; et al.
Abstract : Introduction and Objectives: Attempts to develop standardised guidelines in the management of primary spontaneous pneumothorax (PSP) have been severely hampered by a lack of high quality clinical research. The American College of Chest Physicians (ACCP) and BTS guidelines are based on non-analytical studies and expert opinion. Remarkably, no consensus regarding the definition of PSP severity exists, with the ACCP and BTS each using different arbitrary measurements: hilar size > 2cm (BTS) versus apical size >3cm (ACCP). The objective of this study is to define the critical size of PSP. Methods: A multi-centre prospective comparison of 168 consecutive patients presenting with PSP was performed in 13 NHS hospitals in the East of England over a period of 15 months. We compared the ability of the BTS and ACCP definitions to predict the eventual need for intercostal chest drain (ICD) insertion. Since current BTS guidelines state that pleural aspiration should be attempted prior to drainage in non-compromised PSP patients, we reasoned that ICD insertion was a valid endpoint. Using a logistic regression model that included hospital, age, hilar size, apical size and the hilar-apical interaction, we generated receiver operating characteristic (ROC) curves reflecting the probability of either measure correctly predicting the eventual need for ICD. Results: One hundred and sixteen of 168 patients for whom data were collected had been treated according to BTS guidelines. Of these, 39 eventually required ICD insertion. The correlation between hilar and apical distances was high (0.7). The logistic regression showed that hilar distance was statistically significant (p < 0.001), but apical distance and the interaction were not. The sensitivity and specificity from using BTS guidelines were 0.667 (95% CI 0.510–0.794) and 0.805 (0.703–0.878) respectively, whereas the same values using the ACCP guidelines were 0.948 (0.831–0.986) and 0.351 (0.253–0.462). Conclusion: Guidelines based on hilar distance, such as the BTS's, are likely to be more informative in predicting the eventual need for ICD. However, the two distances are highly correlated. This study, for the first time, provides an evidence-based clinically relevant definition of PSP requiring ICD that will guide treatment and serve as the foundation for subsequent trials.